Potentialisation of the bupivacaine antioxidant effects by lactate ringer's solution infusion during spinal anaesthesia in rams - Kamiloglu, N.N.; Beytut, E.; Kamilo?lu, A.; Aksakal, M.; Güven, A. (My University, 2007)
The objective of this study was to determine if the infusion of lactated Ringer's (LR) solution before and during spinal anaesthesia with bupivacaine would improve the efficiency of enzymatic (glutathione peroxidase, catalase) and non enzymatic (glutathione, vitamins A and E) antioxidant systems and would attenuate lipid peroxidation measured as plasma concentrations of thiobarbituric acid substances (TBARS) in rams. The experiment was carried out on 15 clinically healthy adult male Tuj sheep. LR (12 ml/kg over 20 min) was infused via the jugular vein 20 min prior spinal anaesthesia (SA) induced by 8 ml of 0.5% bupivacaine solution in the group I (n = 5), or immediately after in the group II (n = 5), whereas only SA was induced in the control group (group III, n = 5). Plasma TBARS and vitamin A and E concentrations, erythrocyte glutathione (GSH) concentrations and glutathione peroxidase (GSHPX; EC: 1.11.1.9), as well as catalase (CAT) activity in the spinal fluid were measured before anaesthesia (zero min), and at 5, 15, 30 and 60 min. after. Whereas plasma TBARS concentrations remained constant in the 2 groups infused with LR (groups I and II), they gradually increased in the control group (p < 0.001). The progressive declines of plasma vitamin A and E concentrations according to time were less marked in the groups I and II compared to the group III (p < 0.01 at 30 and 60 min.). Furthermore, plasma vitamin E concentrations remained more elevated in the group II than in the groups I and III at 30 and 60 min. (p < 0.01). On the contrary, gradual increases of erythrocyte GSH concentrations and GSH-Px activities according to time were observed in all groups, but these effects were more intense in rams infused with LR. In the same way, CAT activity in spinal fluid progressively increased in the groups I and II while it was not modified by SA alone (group III). Taken together, these results suggest that LR infusion coupled to bupivacaine administration has reduced the occurrence of lipid peroxidation by up regulation of enzymatic antioxidant systems (GSH-Px, CAT) and by limiting utilisation of non enzymatic systems (vitamins A and E).
Keywords: Antioxidant system; Bupivacaine; Lactate Ringer's solution; Lipid peroxidation; Ram; Spinal anaesthesia